The Collapse of Silicon Valley Bank - Vijaya Kittu Manda (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2023)
Purpose: The collapse of any bank in any country will bring several ramifications to a country's banking services and economy. Because of the global connectedness of financial services, risk can become contagious. The collapse of three small-to-mid-size banks in the U.S. during March 2023 has lessons for the global banking industry and regulators to learn. The case examines the series of happenings that led to the collapse of the Silicon Valley Bank (SVB), the moves made by the management to prevent a bank run situation, the interference of banking insurance, take over by First Citizens BancShares, and developments around it. Important lessons learned by different stakeholders are reported. Method: This study employs a case study approach in qualitative research. The evaluation has considered the developments around the collapsed bank and its aftermath. Media sources are used to track the developments and are supported by academic references whenever possible. The research has taken note of the happenings between March and July of 2023. Result: The study finds that while global stock markets are turbulent because of the banking crisis, they subsided in due course. The acquisition of SVB by First Citizens has reduced the panic situation. Customers in other countries, including the U.K., had to seek governmental and legal interventions. The collapse of SVB impacted the cryptocurrency segment in the U.S. Competitor banks appear to have taken advantage of the situation. Novelty: The study will be amongst the first to examine the collapse of the SVB from multiple dimensions of running a bank. It contributes to the academic research on banking crisis and contingency risk studies.